Repeated barrier drown-out is required to facilitate long-distance migration of a potamodromous fish - Jason D. Thiem; Benjamin G. Fanson; David Ryan; Gavin L. Butler; David A. Crook; Doug J. Harding; Anthony Townsend; Ian J. Wooden; Ivor Stuart (Aquatic Sciences, 2025)
Migratory fish species are highly vulnerable to stream fragmentation. Potamodromous golden perch ( Macquaria ambigua ) inhabit the barrier-laden Murray–Darling Basin (MDB), Australia’s largest river system, and its lifecycle includes a requirement for uninterrupted stretches of flowing water habitat. Owing to these barriers, large-scale connectivity in many regions is limited to periods of high flow events that facilitate barrier drown-out. We undertook a 3-year (2021–2024) study using telemetry to quantify the movements of 150 adult golden perch from the Barwon–Darling River over a period that encompassed numerous high flow events and flooding. Approximately 75% of tagged golden perch undertook movements > 50 km, with > 90% of movements in an upstream direction, extending up to 1500 km and associated with increased river discharge. Tributary entries were detected on multiple occasions, with an apparent preference for specific tributaries. Ten fish migrated > 1000 km upstream across multiple flow events. The results of this study (1) highlight the importance of the Barwon–Darling River and tributaries as a key migration conduit for adult golden perch, (2) demonstrate that multiple flow events are required to achieve large-scale dispersal and (3) provide quantitative flow-movement relationships that can be used to support inter-regional management actions. These management actions might include barrier removal, the construction of fishways and protection of tributary–mainstem flow events.

GLOSSAQUA : A global dataset of size spectra across aquatic ecosystems - Zeynep Ersoy; Charlotte Evangelista; Aitor Larrañaga; Daniel M. Perkins; Javier Sánchez‐Hernández; Teofana Chonova; David Cunillera‐Montcusí; Carmen García‐Comas; Jorge García‐Girón; Ioar de Guzman; Justin Pomeranz; Victor Saito; et al. (Ecology, 2025)
Body size is a key trait in ecology due to its influence on metabolism and many other life‐history traits that affect population and community responses to environmental variation as well as ecosystem properties. The size spectrum represents the relationship between abundance (or biomass) and body size, independent of species identity. Size spectrum parameters, such as the slope or intercept, have been applied extensively as indicators of ecological status across multiple ecosystem types. The GLOSSAQUA dataset includes data from mainly heterotrophic communities composed of single (e.g., zooplankton, macroinvertebrates, or fish) to multiple taxonomic groups (e.g., from primary consumers to apex predators, and phytoplankton to large zooplankton), across diverse spatial and temporal scales, from surveys in freshwater (43% studies), marine (52% studies) and brackish (5% studies) ecosystems. In total, we compiled a unique global dataset of 8459 size spectrum slopes or exponents, 5237 intercepts, and 4,497 linearity coefficients (i.e., defined by the R 2 of the linear fit of the size spectrum) from 127 articles and gray literature (i.e., unpublished datasets). The current dataset aims to help identify the main drivers shaping aquatic size spectrum parameters at a global scale and contribute to cross‐ecosystem comparisons. GLOSSAQUA can serve to explore questions such as factors influencing spatial and temporal dynamics of community size structure, comparing the response of community size structure between natural versus human‐impacted sites, and comparing global patterns in different aquatic ecosystems. We encourage researchers, especially those from underrepresented geographical areas (e.g., South Hemisphere and Asia) to fuel this dataset in the future. The dataset is provided under a CC‐BY‐NC‐S4 4.0 license, and users are encouraged to cite this data paper when using the data.

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

High-altitude characterization of the Hunga pressure wave with cosmic rays by the HAWC observatory - Ruben Alfaro; César Alvarez; Juan Carlos Arteaga-Velázquez; Arun Babu Kollamparambil Paul; Daniel Avila Rojas; Hugo Alberto Ayala Solares; Rishi Babu; Ernesto Belmont-Moreno; Chad Brisbois; Karen S. Caballero-Mora; Tomás Capistrán; Alberto Carramiñana; et al. (Advances in Space Research, 2024)

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

Schomburginones A‒J, geranylated benzophenones from the leaves of Garcinia schomburgkiana and their cytotoxic and anti-inflammatory activities - Edwin R. Sukandar; Sutin Kaennakam; Sutthida Wongsuwan; Jaruwan Chatwichien; Sucheewin Krobthong; Yodying Yingchutrakul; Thanisorn Mahatnirunkul; Fadjar Mulya; Vudhichai Parasuk; David J. Harding; Preeyaporn Poldorn; Thanyada Rungrotmongkol; et al. (Phytochemistry, 2023)

Experimental support for reclassification of the light scattering second virial coefficient from macromolecular solutions as a hydrodynamic parameter - Donald J. Winzor; Vlad Dinu; David J. Scott; Stephen E. Harding (European Biophysics Journal, 2023)
This investigation examines the source of the disparity between experimental values of the light scattering second virial coefficient $${A}_{2}$$ A 2 (mL.mol/g 2 ) for proteins and those predicted on the statistical mechanical basis of excluded volume. A much better theoretical description of published results for lysozyme is obtained by considering the experimental parameters to monitor the difference between the thermodynamic excluded volume term and its hydrodynamic counterpart. This involves a combination of parameters quantifying concentration dependence of the translational diffusion coefficient obtained from dynamic light scattering measurements. That finding is shown to account for observations of a strong correlation between $${A}_{2}{M}_{2}$$ A 2 M 2 (mL/g), where M 2 is the molar mass (molecular weight) of the macromolecule and the diffusion concentration parameter $${k}_{D}$$ k D (mL/g). On the grounds that $${k}_{D}$$ k D is regarded as a hydrodynamic parameter, the same status should be accorded the light scattering second virial coefficient rather than its current incorrect thermodynamic designation as $${B}_{2}$$ B 2 (mL.mol/g 2 ), or just B , the osmotic second virial coefficient for protein self-interaction.

Retrospective rationalization of disparities between the concentration dependence of diffusion coefficients obtained by boundary spreading and dynamic light scattering - Donald J. Winzor; Vlad Dinu; David J. Scott; Stephen E. Harding (European Biophysics Journal, 2023)
This study establishes the existence of substantial agreement between published results from traditional boundary spreading measurements (including synthetic boundary measurements in the analytical ultracenrifuge) on two globular proteins (bovine serum albumin, ovalbumin) and the concentration dependence of diffusion coefficient predicted for experiments conducted under the operative thermodynamic constraints of constant temperature and solvent chemical potential. Although slight negative concentration dependence of the translational diffusion coefficient is the experimentally observed as well as theoretically predicted, the extent of the concentration dependence is within the limits of experimental uncertainty inherent in diffusion coefficient measurement. Attention is then directed toward the ionic strength dependence of the concentration dependence coefficient ( $${k}_{D}$$ k D ) describing diffusion coefficients obtained by dynamic light scattering, where, in principle, the operative thermodynamic constraints of constant temperature and pressure preclude consideration of results in terms of single-solute theory. Nevertheless, good agreement between predicted and published experimental ionic strength dependencies of $${k}_{D}$$ k D for lysozyme and an immunoglobulin is observed by a minor adaptation of the theoretical treatment to accommodate the fact that thermodynamic activity is monitored on the molal concentration scale because of the constraint of constant pressure that pertains in dynamic light scattering experiments.

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Secondary metabolites from cultures of the ant pathogenic fungus Ophiocordyceps irangiensis BCC 2728 - Siriporn Saepua; Jittra Kornsakulkarn; Patchanee Auncharoen; Pranee Rachtawee; Surisa Kongthong; Nattawut Boonyuen; David J. Harding; Tatsuo Nehira; Tienthong Thongpanchang; Chawanee Thongpanchang (Natural Product Research, 2021)

The genetic architecture of target‐site resistance to pyrethroid insecticides in the African malaria vectors Anopheles gambiae and Anopheles coluzzii - Chris S. Clarkson; Alistair Miles; Nicholas J. Harding; Andrias O. O’Reilly; David Weetman; Dominic Kwiatkowski; Martin J. Donnelly (Molecular Ecology, 2021)
Resistance to pyrethroid insecticides is a major concern for malaria vector control. Pyrethroids target the voltage‐gated sodium channel (VGSC), an essential component of the mosquito nervous system. Substitutions in the amino acid sequence can induce a resistance phenotype. We use whole‐genome sequence data from phase 2 of the Anopheles gambiae 1000 Genomes Project (Ag1000G) to provide a comprehensive account of genetic variation in the Vgsc gene across 13 African countries. In addition to known resistance alleles, we describe 20 other non‐synonymous nucleotide substitutions at appreciable population frequency and map these variants onto a protein model to investigate the likelihood of pyrethroid resistance phenotypes. Thirteen of these novel alleles were found to occur almost exclusively on haplotypes carrying the known L995F kdr (knock‐down resistance) allele and may enhance or compensate for the L995F resistance genotype. A novel mutation I1527T, adjacent to a predicted pyrethroid‐binding site, was found in tight linkage with V402L substitutions, similar to allele combinations associated with resistance in other insect species. We also analysed genetic backgrounds carrying resistance alleles, to determine which alleles have experienced recent positive selection, and describe ten distinct haplotype groups carrying known kdr alleles. Five of these groups are observed in more than one country, in one case separated by over 3000 km, providing new information about the potential for the geographical spread of resistance. Our results demonstrate that the molecular basis of target‐site pyrethroid resistance in malaria vectors is more complex than previously appreciated, and provide a foundation for the development of new genetic tools for insecticide resistance management.

Synthesis, characterization and anticancer activity of Fe(II) and Fe(III) complexes containing N-(8-quinolyl)salicylaldimine Schiff base ligands - Sutthida Wongsuwan; Jaruwan Chatwichien; Bussaba Pinchaipat; Sarawut Kumphune; David J. Harding; Phimphaka Harding; Jaursup Boonmak; Sujittra Youngme; Ratanon Chotima (JBIC Journal of Biological Inorganic Chemistry, 2021)

Quantifying the concentration dependence of sedimentation coefficients for globular macromolecules: a continuing age-old problem - Donald J. Winzor; Vlad Dinu; David J. Scott; Stephen E. Harding (Biophysical Reviews, 2021)
This retrospective investigation has established that the early theoretical attempts to directly incorporate the consequences of radial dilution into expressions for variation of the sedimentation coefficient as a function of the loading concentration in sedimentation velocity experiments require concentration distributions exhibiting far greater precision than that achieved by the optical systems of past and current analytical ultracentrifuges. In terms of current methods of sedimentation coefficient measurement, until such improvement is made, the simplest procedure for quantifying linear s - c dependence (or linear concentration dependence of 1/ s ) for dilute systems therefore entails consideration of the sedimentation coefficient obtained by standard c ( s ), g* ( s ) or G ( s ) analysis) as an average parameter ( $$ \overline{s} $$ s ¯ ) that pertains to the corresponding mean plateau concentration (following radial dilution) ( $$ \overline{c} $$ c ¯ ) over the range of sedimentation velocity distributions used for the determination of $$ \overline{s} $$ s ¯ . The relation of this with current descriptions of the concentration dependence of the sedimentation and translational diffusion coefficients is considered, together with a suggestion for the necessary improvement in the optical system.

Development of a pro-arrhythmic ex vivo intact human and porcine model: cardiac electrophysiological changes associated with cellular uncoupling - Joseph Brook; Min-young Kim; Simos Koutsoftidis; David Pitcher; Danya Agha-Jaffar; Annam Sufi; Catherine Jenkins; Konstantinos Tzortzis; Suofeiya Ma; Richard J. Jabbour; Charles Houston; Balvinder S. Handa; et al. (Pflügers Archiv - European Journal of Physiology, 2020)
We describe a human and large animal Langendorff experimental apparatus for live electrophysiological studies and measure the electrophysiological changes due to gap junction uncoupling in human and porcine hearts. The resultant ex vivo intact human and porcine model can bridge the translational gap between smaller simple laboratory models and clinical research. In particular, electrophysiological models would benefit from the greater myocardial mass of a large heart due to its effects on far-field signal, electrode contact issues and motion artefacts, consequently more closely mimicking the clinical setting. Porcine ( n = 9) and human ( n = 4) donor hearts were perfused on a custom-designed Langendorff apparatus. Epicardial electrograms were collected at 16 sites across the left atrium and left ventricle. A total of 1 mM of carbenoxolone was administered at 5 ml/min to induce cellular uncoupling, and then recordings were repeated at the same sites. Changes in electrogram characteristics were analysed. We demonstrate the viability of a controlled ex vivo model of intact porcine and human hearts for electrophysiology with pharmacological modulation. Carbenoxolone reduces cellular coupling and changes contact electrogram features. The time from stimulus artefact to (-dV/dt) max increased between baseline and carbenoxolone (47.9 ± 4.1–67.2 ± 2.7 ms) indicating conduction slowing. The features with the largest percentage change between baseline and carbenoxolone were fractionation + 185.3%, endpoint amplitude − 106.9%, S-endpoint gradient + 54.9%, S point − 39.4%, RS ratio + 38.6% and (-dV/dt) max − 20.9%. The physiological relevance of this methodological tool is that it provides a model to further investigate pharmacologically induced pro-arrhythmic substrates.

Taxonomy of the order Mononegavirales: update 2017 - Gaya K. Amarasinghe; Yīmíng Bào; Christopher F. Basler; Sina Bavari; Martin Beer; Nicolás Bejerman; Kim R. Blasdell; Alisa Bochnowski; Thomas Briese; Alexander Bukreyev; Charles H. Calisher; Kartik Chandran; et al. (Archives of Virology, 2017)

Application of novel analytical ultracentrifuge analysis to solutions of fungal mannans - Richard B. Gillis; Gary G. Adams; David T. M. Besong; Eva Machová; Anna Ebringerová; Arthur J. Rowe; Stephen E. Harding; Trushar R. Patel (European Biophysics Journal, 2017)

Contrasting patterns in growth and survival of Central Valley fall run Chinook salmon related to hatchery and ocean conditions - Megan C. Sabal; David D. Huff; Mark J. Henderson; Jerome Fiechter; Jeffrey A. Harding; Sean A. Hayes (Environmental Biology of Fishes, 2016)

Early ocean distribution of juvenile Chinook salmon in an upwelling ecosystem - Jason L. Hassrick; Mark J. Henderson; David D. Huff; William J. Sydeman; Megan C. Sabal; Jeffrey A. Harding; Arnold J. Ammann; Eric D. Crandall; Eric P. Bjorkstedt; John Carlos Garza; Sean A. Hayes (Fisheries Oceanography, 2016)
Extreme variability in abundance of California salmon populations is often ascribed to ocean conditions, yet relatively little is known about their marine life history. To investigate which ocean conditions influence their distribution and abundance, we surveyed juvenile Chinook salmon ( Oncorhynchus tshawytscha ) within the California Current (central California [37°30′N) to Newport, Oregon (44°00′N]) for a 2‐week period over three summers (2010–2012). At each station, we measured chlorophyll‐ a as an indicator of primary productivity, acoustic‐based metrics of zooplankton density as an indicator of potential prey availability and physical characteristics such as bottom depth, temperature and salinity. We also measured fork lengths and collected genetic samples from each salmon that was caught. Genetic stock identification revealed that the majority of juvenile salmon were from the Central Valley and the Klamath Basin (91–98%). We constructed generalized logistic‐linear negative binomial hurdle models and chose the best model(s) using Akaike's Information Criterion ( AIC ) to determine which covariates influenced the salmon presence and, at locations where salmon were present, determined the variables that influenced their abundance. The probability of salmon presence was highest in shallower waters with a high chlorophyll‐ a concentration and close to an individual's natal river. Catch abundance was primarily influenced by year, mean fork length and proximity to natal rivers. At the scale of sampling stations, presence and abundance were not related to acoustic indices of zooplankton density. In the weeks to months after ocean entry, California's juvenile Chinook salmon population appears to be primarily constrained to coastal waters near natal river outlets.

Region‐wide changes in marine ecosystem dynamics: state‐space models to distinguish trends from step changes - Matthew Spencer; Nova Mieszkowska; Leonie A. Robinson; Stephen D. Simpson; Michael T. Burrows; Silvana N. R. Birchenough; Eva Capasso; Polly Cleall‐Harding; Julia Crummy; Callan Duck; Damien Eloire; Matthew Frost; et al. (Global Change Biology, 2012)
Regime shifts are sudden changes in ecosystem structure that can be detected across several ecosystem components. The concept that regime shifts are common in marine ecosystems has gained popularity in recent years. Many studies have searched for the step‐like changes in ecosystem state expected under a simple interpretation of this idea. However, other kinds of change, such as pervasive trends, have often been ignored. We assembled over 300 ecological time series from seven UK marine regions, covering two to three decades. We developed state‐space models for the first principal component of the time series in each region, a common measure of ecosystem state. Our models allowed both trends and step changes, possibly in combination. We found trends in three of seven regions and step changes in two of seven regions. Gradual and sudden changes are therefore important trajectories to consider in marine ecosystems.

Adverse foraging conditions may impact body mass and survival of a high Arctic seabird - Ann M. A. Harding; Jorg Welcker; Harald Steen; Keith C. Hamer; Alexander S. Kitaysky; Jérôme Fort; Sandra L. Talbot; Leslie A. Cornick; Nina J. Karnovsky; Geir W. Gabrielsen; David Grémillet (Oecologia, 2011)

Cryoconservation of South African plant genetic diversity - Patricia Berjak; Paul Bartels; Erica E. Benson; Keith Harding; David J. Mycock; Norman W. Pammenter; Sershen; James Wesley-Smith (In Vitro Cellular & Developmental Biology - Plant, 2011)

Lidar remote sensing of above‐ground biomass in three biomes - Michael A. Lefsky; Warren B. Cohen; David J. Harding; Geoffrey G. Parker; Steven A. Acker; S. Thomas Gower (Global Ecology and Biogeography, 2002)
Estimation of the amount of carbon stored in forests is a key challenge for understanding the global carbon cycle, one which remote sensing is expected to help address. However, estimation of carbon storage in moderate to high biomass forests is difficult for conventional optical and radar sensors. Lidar ( li ght d etection and r anging) instruments measure the vertical structure of forests and thus hold great promise for remotely sensing the quantity and spatial organization of forest biomass. In this study, we compare the relationships between lidar‐measured canopy structure and coincident field measurements of above‐ground biomass at sites in the temperate deciduous, temperate coniferous, and boreal coniferous biomes. A single regression for all three sites is compared with equations derived for each site individually. The single equation explains 84% of variance in above‐ground biomass ( P

Correction - Sijun Liu; Ian D. Bedford; Peter G. Markham; Morad Ghanim; Muhamad Zeidan; Henryk Czosnek; A. Bruyère; E. Herrbach; V. Brault; V. Ziegler-Graff; H. Guilley; J. F. J. M. Heuvel; et al. (Phytoparasitica, 1998)

Abstracts of presentations on plant protection issues at the xth international congress of virology - Sijun Liu; Ian D. Bedford; Peter G. Markham; Morad Ghanim; Muhamad Zeidan; Henryk Czosnek; A. Bruyère; E. Herrbach; V. Brault; V. Ziegler-Graff; H. Guilley; J. F. J. M. van den Heuvel; et al. (Phytoparasitica, 1998)

Abstracts of presentations on plant protection issues at the xth international congress of virology - E. Ramirez; A. Hernádez; E. Ham; B. L. Barrón; S. W. Ding; W. X. Li; B. J. Shi; R. H. Symons; Q. Li; K. H. Ryu; P. Palukaitis; I. B. Kaplan; et al. (Phytoparasitica, 1997)

A polydisperse linear random coil model for the quaternary structure of pig colonic mucin - Kornelia Jumel; Fiona J. J. Fogg; David A. Hutton; J. P. Pearson; Adrian Allen; S. E. Harding (European Biophysics Journal, 1997)

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)